Serum Interleukin-26 Is a New Biomarker for Disease Activity Assessment in Systemic Lupus Erythematosus - Brilland, Benoit; Bach-Bunner, Maxime; Gomes, Christopher Nunes; Larochette, Vincent; Foucher, Etienne; Plaisance, Marc; Saulnier, Patrick; Costedoat-Chalumeau, Nathalie; Ghillani, Pascale; Belizna, Cristina; Delneste, Yves; Augusto, Jean-François; et al. (Frontiers in Immunology, 2021)
Objective: Interleukin-26 (IL-26) has a unique ability to activate innate immune cells due to its binding to circulating double-stranded DNA. High levels of IL-26 have been reported in patients with chronic inflammation. We aimed to investigate IL-26 levels in patients with systemic lupus erythematosus (SLE). Methods: IL-26 serum levels were quantified by ELISA for 47 healthy controls and 109 SLE patients previously enrolled in the PLUS study. Performance of IL-26 levels and classical markers (autoantibodies or complement consumption) to identify an active SLE disease (SLE disease activity index (SLEDAI) score > 4) were compared. Results: IL-26 levels were significantly higher in SLE patients than in controls (4.04 ± 11.66 and 0.74 ± 2.02 ng/mL; p = 0.005). IL-26 levels were also significantly higher in patients with active disease than those with inactive disease (33.08 ± 21.06 vs 1.10 ± 3.80 ng/mL, p < 0.0001). IL-26 levels correlated with SLEDAI score and the urine protein to creatinine ratio (uPCR) (p < 0.001). Patients with high IL-26 levels had higher SLEDAI score, anti-DNA antibodies levels, and uPCR (p < 0.05). They presented more frequently with C3 or C4 complement consumption. Lastly, IL-26 showed stronger performance than classical markers (complement consumption or autoantibodies) for active disease identification. Conclusions: Our results suggest that, in addition to classical SLE serological markers, the measurement of IL-26 levels may be a useful biomarker for active disease identification in SLE patients.